STRATEGI RANTAI PASOKAN BUKU UNTUK PEMBERDAYAAN PERPUSTAKAAN DUSUN KETANDAN, DESA MADUREJO, KECAMATAN PRAMBANAN, KABUPATEN SLEMAN - Mega Inayati Rif'ah; Hendra Saputra; Idham Alfassyakur (DHARMA BAKTI, 2020)
Madurejo Village is one of the villages in Prambanan District, Sleman Regency. Karang Taruna "Citra Muda" is youth organization in Madurejo, which has the potential to be developed. One of the main programs of Karang Taruna ‘Citra Muda’ is the Village Library, but the obstacle is inadequate book supply. The books that currently exist are modest donations from local residents, and most them are old editions (more than 10 years). So, the aim of this community service is giving Karang Taruna 'Citra Muda' a counseling about the book supply chain strategy. The results of this community service is Karang Taruna 'Citra Muda' can find out which organizations provide free book supply services, and then the participants are also able to make proposals for requesting book supplies from the organizations.